Preferences of smart shopping channels and their impact on perceived wellbeing and social inclusion - Papagiannidis, Savvas; Bourlakis, Michael; Alamanos, E.; Dennis, C. (Elsevier, 2017)
This study examines consumers’ interactions with retailers via three different shopping channels. Two of the channels are “smart” (technological) channels, comprising (i) where consumers shop using a computer and (ii) where consumers shop using a mobile phone. These two channels are compared with (iii) the traditional store channel. The paper explores the effect that consumers’ interactions with these channels has on their wellbeing, with a focus on individuals who perceive themselves as being socially excluded, for example, lacking access to goods, services and information. We make a connection between social exclusion and channel contribution to wellbeing for multiple channels, through the lens of the Theory of Planned Behaviour. The online survey findings (n = 1368) indicate that for each channel, there is a higher contribution to wellbeing for that channel for people who are more socially excluded. Social exclusion can have many underlying causes, but channel contributions to wellbeing remain for consumers suffering from financial stress and also those with mobility disability. For the mobile phone channel, the positive channel contributions to wellbeing are greater for younger than for older people. The paper outlines the implications for scholars and practitioners.
Keywords: Multi-channel shopping; Smart shopping channels; Online shopping; Social commerce; Social exclusion; Wellbeing